2001
DOI: 10.1309/k5p2-4y8b-7l5a-faa9
|View full text |Cite
|
Sign up to set email alerts
|

Multiprobe FISH for Enhanced Detection of Bladder Cancer in Voided Urine Specimens and Bladder Washings

Abstract: The aim of this study was to evaluate the UroVysion (Vysis, Downers Grove, IL) fluorescence in situ hybridization (FISH) test for improved detection of bladder cancer in urinary specimens. Three groups of specimens were examined, including voided urine specimens (1) collected before resection of bladder cancer, (2) from cystoscopically negative bladders of patients with previous bladder cancer, and (3) from patients with benign prostatic hyperplasia (controls). FISH positivity was defined as more than 2 urothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
153
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 210 publications
(163 citation statements)
references
References 19 publications
6
153
1
3
Order By: Relevance
“…9,25 Urovysiont FISH is one such molecular test that has been shown to have high sensitivity and specificity for the detection of urothelial carcinoma in urine. 8,14,19,21,26 We recently observed several cases of non-urothelial carcinoma that were Urovysiont FISH-positive. Others have also observed these coincidental overlaps with non-urothelial tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,25 Urovysiont FISH is one such molecular test that has been shown to have high sensitivity and specificity for the detection of urothelial carcinoma in urine. 8,14,19,21,26 We recently observed several cases of non-urothelial carcinoma that were Urovysiont FISH-positive. Others have also observed these coincidental overlaps with non-urothelial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Urovysiont FISH has a reported sensitivity of 73-92%, a specificity of 89-96% for urothelial carcinoma detection and several studies have confirmed its usefulness in the diagnosis and surveillance of these tumors. 8,14,[19][20][21][22] The test is designed to detect aneuploidy for chromosomes 3, 7, 17, and loss of the 9p21 locus in malignant urothelial cells that are shed in the urine of persons with urothelial carcinoma. These represent some of the most common chromosomal abnormalities in urothelial carcinoma.…”
mentioning
confidence: 99%
“…Such marker panel could be utilized for more specific molecular urine screening with microsatellite analyses 63 or interphase multicolor FISH. 64,65 The frequent chromosomal losses on 8p12-22 in many malignancies strongly suggest the presence of important tumor suppressor genes within this region. In bladder cancer, only three candidate genes have been investigated so far.…”
Section: Discussionmentioning
confidence: 99%
“…FISH is increasingly used by cytologists to identify neoplastic cells in various cytological specimens and has been shown to be more sensitive than conventional cytology for the detection of bladder cancer in urine specimens and biliary tract malignancy in endoscopic brushing specimens of the biliary tract. [12][13][14][15] FISH performed on esophageal brushing specimens may offer a more practical and accurate surveillance tool for patients with Barrett's esophagus because endoscopic brushing specimens can be obtained more rapidly than four-quadrant biopsies and can sample a larger percentage of the affected area. 13,16 Studies that used FISH to detect bladder cancer in urine specimens used a probe set that was tailored specifically for the detection of bladder cancer.…”
mentioning
confidence: 99%